Information management in passenger traffic supporting system design as a multi-criteria discrete optimization task - Galuszka, Adam; Krystek, Jolanta; Swierniak, Andrzej; Lungoci, Carmen; Grzejszczak, Tomasz (Archives of Control Sciences, 2017)
This paper presents a concept of an Integrated System of Supporting Information Management in Passenger Traffic (ISSIMPT). The novelty of the system is an integration of six modules: video monitoring, counting passenger flows, dynamic information for passengers, the central processing unit, surveillance center and vehicle diagnostics into one coherent solution. Basing on expert evaluations, we propose to present configuration design problem of the system as a multi-objectives discrete static optimization problem. Then, hybrid method joining properties of weighted sum and ε-constraint methods is applied to solve the problem. Solution selections based on hybrid method, using set of exemplary cases, are shown.